2018
DOI: 10.3233/jad-180266
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Viruses and Senile Dementia: First Population Evidence for a Causal Link

Abstract: Three articles have very recently appeared that are of especial relevance to the causes of dementia and its potential treatment. The first two (Tsai et al., published in PLoS One in November 2017; Chen et al., published in the January/February 2018 issue of Journal of Clinical Psychiatry) demonstrate an increased risk of subsequent senile dementia (SD) development in patients with acute varicella zoster (herpes zoster) infection. These articles present data highly relevant to the third, and most important, pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Studies showed that a high proportion of the older people who were infected by AD had HSV1 in their brains that could be detected by polymerase chain reaction. 9 Further reviews stated that the HSV1 was predominantly absent in younger people and was mainly seen in older people. The main class of HSV1 with the presence of APOE e4 carriers was noticed to be found in older people with AD.…”
Section: Signposts Of Hsv1 In the Brainmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies showed that a high proportion of the older people who were infected by AD had HSV1 in their brains that could be detected by polymerase chain reaction. 9 Further reviews stated that the HSV1 was predominantly absent in younger people and was mainly seen in older people. The main class of HSV1 with the presence of APOE e4 carriers was noticed to be found in older people with AD.…”
Section: Signposts Of Hsv1 In the Brainmentioning
confidence: 99%
“…3 The unique character of AD is that it can be influenced by various molecular targets, such as acetylcholinesterase, N-methyl D-aspartate, beta-site amyloid precursor protein cleaving enzyme 1 and glycogen synthase kinase 3 beta. 9 Viral reactivation of HSV1 HSV1 is usually transmitted by oral-to-genital and oral-to-oral contact, causing genital herpes and oral herpes infection, respectively. The formation of plaques and tau phosphorylation is the key factor responsible for the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HSV-1 has been related to various neurodegenerative disorders in the last decade [7], and novel studies have contributed to new data and valuable approaches to understand the mechanisms of neurocognitive pathology. One of the most frequent HSV-1 infection-associated diseases is Alzheimer's disease (AD) [8][9][10][11][12][13]. Life expectancy after diagnosis varies between 7 and 15 years, depending on the severity at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%